Self- Glorification among Sample of secondary schools students in Damascus Governorate (Damascus University Journal of educational and Psychologyical sciences, 2026)
This research aims to identify the level of self- Glorification in a sample of (500) secondary school students. A self- Glorification scale, developed by the researcher, was used to answer the research questions. A set of results was reached, the most Glorification of which are: The level of self- Glorification among the study sample members was high, and the most prevalent type of self- Glorification among the study sample members was digital self- Glorification. Regarding the differences among the study sample members on the self- Glorification scale according to the variables (gender, birth order, level of academic achievement), the differences were in favor of females and in favor of the smallest son. However, the differences were not significant on the same scale according to the variable of level of academic achievement.
Keywords: Self- Promotion; Secondary School Students; Adolescents